2019
DOI: 10.1177/0748233719834150
|View full text |Cite
|
Sign up to set email alerts
|

Mancozeb fungicide-induced genotoxic effects, metabolic alterations, and histological changes in the colon and liver of Sprague Dawley rats

Abstract: The present study was designed to evaluate genotoxic markers of mancozeb exposure and withdrawal in colon and liver tissues together with histological changes in the gastrointestinal tract of Sprague Dawley rats. Thirty rats were divided into three equal groups; group I: treatment, 250 mg/kg mancozeb dissolved in corn oil administered twice weekly for 7 weeks; group II: withdrawal, the same treatment as group I after which animals were untreated for 5 weeks; group III: control, administered corn oil on the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
5
10
0
Order By: Relevance
“…MZ exposure for 15 days increased triglycerides and reduced glucose, glycogen, and trehalose. These results corroborate with Yahia et al (Yahia et al, 2014(Yahia et al, , 2019, who found that MZ increased triglycerides and decreased serum glucose in rats exposed to this fungicide. In the present study, MZ induced weight loss in flies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…MZ exposure for 15 days increased triglycerides and reduced glucose, glycogen, and trehalose. These results corroborate with Yahia et al (Yahia et al, 2014(Yahia et al, , 2019, who found that MZ increased triglycerides and decreased serum glucose in rats exposed to this fungicide. In the present study, MZ induced weight loss in flies.…”
Section: Discussionsupporting
confidence: 91%
“…Studies carried out with rodents demonstrated that exposure to MZ could alter triglycerides and glucose levels in the serum (Yahia et al, 2019). This fact could lead to metabolic disturbances.…”
Section: Resultsmentioning
confidence: 99%
“…Yahia et al 37 used 250-mg/kg mancozeb dissolved in corn oil administered twice weekly for seven weeks and indicated that mancozeb exposure caused an increment in triglycerides, and total cholesterol also decreased glucose levels, resulting in the damage of DNA in the liver and colon with pathological changes in stomach, colon, and liver. In the light of this study, we used a single dosage of 500-mg/kg mancozeb dissolved in corn oil.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have also reported adverse health effects of MZB in experimental mammals such as hepatotoxicity (Saber et al, 2019;Yahia et al, 2019), carcinogenic potential (Belpoggi et al, 2002), neurotoxicity and Parkinson-like symptoms (Domico et al, 2007), dysfunction of thyroid glands (Axelstad et al, 2011), nephrotoxicity, endocrine system disruption in females, and defects in fetal development (Bianchi et al, 2020;Girish and Reddy, 2017;Liu et al, 2017). Male reproductive system disorders such as infertility and spermatogenesis insufficiency has been reported previously.…”
Section: Introductionmentioning
confidence: 81%